OC-122 Enhanced recovery after upper gastrointestinal surgery (ERAUGIS) improves outcomes in upper gastrointestinal (UGI) cancer. (28th May 2012) - Beamish, A J; Chan, D S Y; Reid, T D; Barlow, R; Howell, I; Blackshaw, G; Clark, G; Lewis, W G
Abstract : Introduction: The enhanced recovery after surgery (ERAS) principles of optimising nutrition, minimising the surgical stress response and early mobilisation have been reported to improve outcomes in colorectal surgery, but data in UGI surgery is thin. The aim of this study was to determine the influence on outcomes of an ERAS programme in UGI cancer surgery. Methods: Two hundred and eight consecutive patients, 89 managed in the ERAUGIS programme and 119 historical controls (CON) were studied in this prospective observational cohort study, and the primary outcome measures were hospital length of stay (LoS) and 30-day morbidity (classified according to the Clavien-Dindo (CD) criteria). Results: No significant differences in age (p=0.938), gender (p=0.518), tumour site (p=0.461), radiological stage (p=0.219) or histopathological stage (p=0.116) were identified between the two cohorts. ERAUGIS was associated with significant reductions in: overall LoS (median 12 vs 15 days, p=0.001), critical care LoS (median 1 vs 2 days, p<0.0001) and critical care related cancellations (2.2% vs 8.4%, p=0.004). No significant differences in readmission rate (ERAUGIS vs CON = 11% vs 5%, p=0.134) or CD morbidity class (p=0.089) were observed. Multivariable analysis revealed that ERAUGIS (p<0.0001) and anatomical site of surgery (thoracic vs abdominal, p<0.0001) were independently and significantly associated with hospital LoS. Conclusion: ERAUGIS was associated with a fourfold reduction in CC cancellation rates, halved CC LoS and reduced total LoS by 20% without increasing serious operative morbidity. These findings show that ERAS principles outlined in colorectal surgery can be modified and applied safely to patients diagnosed with UGI cancer with significant patient safety, quality and economic benefits. Competing interests: None declared.